Groundwater control and mud rush prevention for caving mines - Morton, KL; van Heerden, W (Caving 2026: Sixth International Conference on Block and Sublevel Caving, 2026)
Caving methods create drainage of all water from within a predictable radius. The diameter and shape of the radius are functions of the sources of water, the country rock hydraulic conductivity and geological structures which drain towards the caving areas (active and closed). Although some water is advantageous to production rates, too much water creates hazardous conditions and contributes to mud rushes. Understanding the sources of water and monitoring head distribution are essential for the calculation and management of water ingress. Over 45 years, the author has developed a phased approach to mine dewatering design and water management. This has been adapted to support caving operations and used to reduce mud rushes. Flood control requires a top-down approach including surface water management, flow path mapping, stormwater prediction and diversion, and modelling of flood events. This can then be incorporated in the mine’s water risk management strategy and reported in the risk register. Prevention of mud rushes requires a thorough understanding of the causes and hydrogeological environment. Mud rushes have 4 components: presence of mud-forming materials (low-friction material or fines), driving head of water (phreatic surface above a specific maximum level), discharge points present for mud to enter the workings and one or two triggers. Triggers include water pressure head exceeding a target head, seismic events, (natural or manmade), blasting pattern and overdraw. Water is the most important factor. The head of water around a caving area can be monitored, diverted and managed. Numerical modelling, based on a detailed understanding of the groundwater regime, can be used to help predict the pattern of pressure distribution and the range of maximum head for specific configurations of extraction advance. Methods are discussed for achieving improved mine dewatering design and the prevention of the ingress of both water and mud.
Keywords: mud rush; caving; monitoring; in rush; flooding; dewatering; water management; drainage; water balance